Association of lower leukocyte count before thrombolysis with early neurological improvement in acute ischemic stroke patients. (October 2018) - Tian, Canhui; Ji, Zhong; Xiang, Wei; Huang, Xiaomei; Wang, Shengnan; Wu, Yongmin; Pan, Suyue; Zhou, Liang; Deng, Zhen
Highlights: Leukocyte count, CT sign and onset-to-treatment(OTT) time were independently associated with early neurological improvement. The change of NIHSS score after 24 h of thrombolysis correlated with leukocyte count, neutrophil and NLR. A model combined leukocyte count, ischemic CT sign, and OTT was generated to predict non-early neurological improvement. Abstract: Early neurological improvement (ENI) after thrombolysis in acute ischemic stroke is associated with a favorable long-term outcome. With the goal to evaluate ENI, we aimed to investigate whether ENI bears a relationship with routine blood tests before thrombolysis. A total of 240 patients with confirmed early ischemic stroke and intravenous recombinant tissue plasminogen activator (rtPA) treatment were enrolled from two teaching hospitals, between June 2010 and March 2016. The primary endpoint was ENI that was defined as a decrease of National Institutes of Health Stroke Scale (NIHSS) scores ≥4 points or complete recovery in 24 h after thrombolysis. Patients underwent NIHSS score evaluation and head CT scan before and after 24 h of IV rtPA treatment. Blood samples for routine blood tests were drawn at admission before IV rtPA administration. Multivariate regression analysis was used to explore the relationship between test results and ENI. Of the results of routine blood tests, leukocyte count before thrombolysis was found to associated independently with ENI (adjusted odds ratio[adj OR] = 0.894, P = 0.025, 95% CI = 0.810–0.986). Onset-to-treatment time (OTT;adj OR = 0.993, P = 0.003, 95% CI = 0.988–0.997) and negative CT sign (adj OR = 3.975, P < 0.001, 95% CI = 1.916–8.246) both were associated with ENI. The change of NIHSS score after 24 h of thrombolysis correlated with the leukocyte and neutrophil count, and neutrophil-to-lymphocyte ratio. A model that combined leukocyte count, positive CT sign, and OTT was generated to predict non-ENI (AUC = 0.717). Therefore, we determined that the leukocyte count was independently associated with ENI. Predicting non-ENI aid in selecting patients for mechanical thrombectomy after thrombolysis.